Building resilience: analysis of health care leaders’ perspectives on the Covid-19 response in Region Stockholm - Carl Savage; Leonard Tragl; Moa Malmqvist Castillo; Louisa Azizi; Henna Hasson; Carl Johan Sundberg; Pamela Mazzocato (BMC Health Services Research, 2024)
Abstract Background The Covid-19 pandemic has tested health care organizations worldwide. Responses have demonstrated great variation and Sweden has been an outlier in terms of both strategy and how it was enacted, making it an interesting case for further study. The aim of this study was to explore how health care leaders experienced the challenges and responses that emerged during the initial wave of the Covid-19 pandemic, and to analyze these experiences through an organizational resilience lens. Methods A qualitative interview study with 12 senior staff members who worked directly with or supervised pandemic efforts. Transcripts were analyzed using traditional content analysis and the codes directed to the Integrated Resilience Attributes Framework to understand what contributed to or hindered organizational resilience, i.e. how organizations achieve their goals by utilizing existing resources during crises. Results/Findings Organizational resilience was found at the micro (situated) and meso (structural) system levels as individuals and organizations dealt with acute shortages and were forced to rapidly adapt through individual sacrifices, resource management, process management, and communications and relational capacity. Poor systemic resilience related to misaligned responses and a lack of learning from previous experiences, negatively impacted the anticipatory phase and placed greater pressure on individuals and organizations to respond. Conventional crisis leadership could hamper innovation, further cement chronic challenges, and generate a moral tension between centralized directives and clinical microsystem experiences. Conclusions The pandemic tested the resilience of the health care system, placing undue pressure on micro and meso systems responses. With improved learning capabilities, some of this pressure may be mitigated as it could raise the anticipatory resilience potential, i.e. with better health systems learning, we may need fewer heroes. How crisis leadership could better align decision-making with frontline needs and temper short-term acute needs with a longer-term infinite mindset is worth further study.